2013
DOI: 10.4236/ojgas.2013.37056
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of early rebleeding and mortality after acute variceal haemorrhage in patients with cirrhosis

Abstract: The upper gastrointestinal bleeding from esophageal or gastric varices is the most dangerous complication of portal hypertension. The purpose of this study was to identify the predictors of early rebleeding and mortality after a bleeding episode. Patients and Methods: It was a retrospective study including 215 patients admitted in our department of hepatology and gastroenterology at the Hassan II University Hospital of Fez, from January 2001 to January 2010. Results: The mean age of our patients was 51 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…Early rebleeding and mortality rate increase sharply within 6 weeks period then stabilized. Early rebleeding rate in the current study was 25.5%, a similar result reported by Krige et al [12] but it is slightly higher than that in some other studies [3] [13] while it is lower than that in other studies [14] [15].…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Early rebleeding and mortality rate increase sharply within 6 weeks period then stabilized. Early rebleeding rate in the current study was 25.5%, a similar result reported by Krige et al [12] but it is slightly higher than that in some other studies [3] [13] while it is lower than that in other studies [14] [15].…”
Section: Discussionsupporting
confidence: 41%
“…Other studies found that 10 days and 2 weeks mortality rate were 11.5% [15] and 8% [22] respectively. Univariate analysis of clinical variables in this study showed that, hypovolemic shock, ascites, WBCs count, serum bilirubin, serum albumin, ALT, AST, CTP score and MELD score were risk factors associated with 6-week mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Neither age nor gender showed any significant difference between the studied group. This was similar to a previous study [17], On contrary to our results, Charif et al 2013 reported that advanced age was associated with early mortality this difference can be explained by different patients' groups as 79% of their patients had esophageal varices without cirrhosis while all our patients were cirrhotic [19]. While Haukeland et al found that the risk of death was positively associated was age and negatively with female sex this dissimilarity may be attributed to different etiological factors of cirrhosis [20].…”
Section: Discussionsupporting
confidence: 90%
“…The occurrence of re-bleeding during the first five days after the bleeding was significantly associated with early mortality in our study (p=0.011), which is also reported in the other studies. 7,14 Journal of Patan Academy of Health Sciences. 2022Dec;9(3):37-45.…”
Section: Discussionmentioning
confidence: 99%